Characterisation of embedded nano-precipitates by X-ray diffraction imaging and small-angle X-ray scattering. (21st April 2014) - Pelliccia, Daniele; Nikulin, Andrei Y.; Kirby, Nigel; Hester, James
We report on the characterisation of embedded Al2 Cu nanoparticles in Al matrix by X-ray diffraction imaging and small-angle X-ray scattering. We employed direct retrieval of the average morphological characteristics of the nanoparticles from their diffraction pattern. Data suggest the possibility of acquiring truly 3D information with X-ray diffraction imaging. Validation of the results obtained with small-angle X-ray scattering is reported.